Does Packaging in Green Pay off? Role of Green Packaging on Firm Performance: Evidence from a Developing Economy - Moraa, Mayieka Linet; Odaya, Aleri; Nyagol, Michael (International Journal of Supply Chain and Logistics, 2024)
Purpose: Greening supply chains has become important more than ever among business firms carving out competitive niches. With the ever increasing complexity in business operations characterised by demand for higher value, supply chain firms are increasingly turning to green practices to not only achieve better results but also be socially responsible. While this is so, Euro monitor International report, 2020 discloses that globally, the manufacturing sector experienced 4.6% drop in market share by 2021, partly orchestrated by environmental upheavals due to business practices. The study sought to examine whether adopting green packaging pays off by establishing effect of green packaging on firm performance in a developing economy, Kenya. Methodology: The study achieved this through a mixed methods design on a population of 460 managers and 92 CEOs, interacted through a structured questionnaire and interview schedule. Standard linear regression in SPSS version 24 and thematic analysis were adopted. Results show that green packaging has significant positive effect on performance (R2=.394, Î²=.628, p<.05), practically denoting that unit increase of packaging in green results to 0.628 units improvement in performance. Findings: The results provide sufficient evidence that indeed, packaging in green pays off. Further, the paper ground theoretical puts by Hart (1995) that green packaging is a pivotal resource. Unique contributor to theory, policy and practice: We provide interesting conclusions that green packaging pays off, advising managers and industry stakeholders to adopt policies of leveraging it. A research agenda is offered to further scholarly subsequent discussions.